Managerial economics : applications, strategy, and tactics - McGuigan, James R.; Moyer, R. Charles;deB. Harris, Frederick H. (Australia : Cengage Learning Asia Pte Ltd, 2017)
Learn how to think analytically and make better business decisions as a future business leader with the insights found in this book. This timely edition illustrates how today's effective managers apply economic theory and techniques to solve real-world everyday decision problems. The concise new edition offers a comprehensive current approach with cutting-edge coverage of important and relevant management topics.
Part 1: Introduction -- 1.Introduction and goals of the firm -- 2.Fundamental economic concepts -- Part 2: Demand and forecasting -- 3.Demand analysis -- 4.Estimating demand -- 4A. Problems in applying the linear regression model -- 5.Business and economic forecasting -- 6.Managing in the global economy -- 6A.Foreign exchange risk management -- Part 2: Production and cost -- 7.Production economics -- 7A.Production economcis of renewable and exhaustible natural resources, advanced material -- 8.Cost analysis -- 9.Applications of cost theory -- Part 4: Pricing and output decisions: strategy and tactics -- 10.Prices, output and strategy: pure and monopolistic competition -- 11.Price and output determination: monopoly and dominant firms -- 12.Price and output determination: oligopoly -- 13.Best-practice tactics: game theory -- 13A.Entry deterrence and accommodation games -- 14.Pricing techniques and analysis -- 14A. The practice of revenue management -- Part 5: Organizational architecture and regulation -- 15.Contracting, governance and organizational form -- 16.Government regulation -- 17.Long-term investment analysis.
Includes index.
Keywords: MANAGERIAL ECONOMICS